518 myRESEARCHpath: an interactive roadmap for navigating research process, resources, and policies at Duke University. (April 2022) - Wylie, Jamie; Brouwer, Rebecca; Jones, Derek; Patil, Sunita
Abstract : OBJECTIVES/GOALS: In 2021, Duke University expanded the myRESEARCHsuite (MRS) of research support services with the launch of myRESEARCHpath (MRP), an interactive roadmap for navigating the project lifecycle. MRP integrates with the existing MRS services, which include a personalized research portal (myRESEARCHhome) and team of experts (myRESEARCHnavigators). METHODS/STUDY POPULATION: MRP was developed as a collaborative effort to centralize essential research-related information across Duke University into one location. MRP provides a web-based platform to integrate policies, processes, and resources from over 40 research support offices, organized into topic-based pages throughout the project lifecycle. Each topic-based page provides integrated guidance, categorized related resources, and contact information for personalized support from subject matter experts. Additional features of MRP include a curated search function, and filters that refine the topic-based pages and related resources to only those applicable to selected project inclusions and organizational unit. RESULTS/ANTICIPATED RESULTS: Since the launch of MRP in January 2021 through the third quarter of 2021, 5, 947 unique users accessed MRP for a total of 17, 452 sessions. The most commonly accessed topic-based pages during this time period were: Activity disclosures (Other Support and Current and Pending) – 3, 231 pageviews Animal welfare – 1, 882 pageviews Proposal review and submission – 1, 306 pageviews NIH research grants (R series) – 686 pageviews Proposal planning – 669 pageviews The most frequently searched terms (including spelling variants) were Other Support, Biosketch, NIH, and no-cost extensions. DISCUSSION/SIGNIFICANCE: This data suggests users are accessing MRP for guidance on new or recently updated requirements. Maintaining clear, unified, and current site content should be prioritized to continue emphasizing MRP as a central location for research-related information. Duke also plans to explore further integration of MRP with the other MRS services.